Study on Environment and Energy Using Belonging Materials - Kobayashi, T; Kanematsu, H; Hashimoto, R; Morisato, K; Ohashi, N; Yamasaki, H; Takamiya, S (International Journal of Sustainable Development & World Policy, 2013)
A trial to quantify CO2 emission by utilizing our belonging materials has been conducted. For the Polymer electrode membrane Fuel Cell (PEFC) system, the reduction of more than 23% CO2 emission was measured under a practical operation in a family of Okayama prefecture. The statistical data of the CO2 emission obtained from the student’s homes has shown that the highest CO2 emission results from the commercial electric power, then gasoline for automobile and kerosene follow thereafter, which is consistent with the trend of the average aspect in Japan. In terms of the high efficiency lighting, the plane lighting source like Organic LED is ideal in view of heat transfer, and the multiple point lighting source is more advantageous than the small number of point lighting source.